An Effective Method for Mapping Web User Profile based on Domain Ontology - M Ratheeshkumar, A.; Rajkumar, M.; Balakrishnan, S.; R Kalaiarasan, T. (International Journal of Engineering and Technology, 2018)
Ontology is characterized as ideas, characteristics and relations that can be utilized to depict and speak to a territory of learning. The main aim of this paper is to create a personalized ontology for web information gathering using language processing techniques. Models use just learning from a worldwide or client's nearby data while speaking to the client profiles. Keeping in mind the end goal to make client's neighboring case archives for coordinating with the portrayal of a worldwide learning base and also to build up a combined ontology using strategies like ontology mapping technique, text categorization, jakard and cosine similarity methods are used to evaluate the efficiency.Â Â